Analysis of the prevalence and pattern of polypharmacy among elderly patients admitted in general medicine department of a rural tertiary care hospital in South India - Gulam Mohammad; Shivangna Singh; Priti Singh; Vivek Gautam; Vijai Ananth Pitchai Pillai (Asian Journal of Medical Sciences, 2023)
Background: Quality and safety of prescribing drugs in older people remain a global healthcare concern. Inappropriate prescribing pattern in the elderly population is now considered as a major public health issue and polypharmacy is one of the common problems among the elderly patients. Aims and Objectives: The aims of this study were (1) to analyze the prevalence, pattern of polypharmacy with respect to age, and gender among the elderly patients and (2) to evaluate the most frequently prescribed drugs in the geriatric population. Materials and Methods: This prospective, cross-sectional, and observational study was conducted among the elderly patients admitted in the Department of General Medicine, Dhanalakshmi Srinivasan Medical College and Hospital, Perambalur, Tamil Nadu. The duration of research project was 12 months from May 2018 to April 2019; approval for the study was taken from the Institutional Ethical Committee. Data on total number of prescribed drugs and main and adjuvant drugs prescribed to patients during treatment were collected and analyzed. Results: A total of 289 patients, that is, 167 male and 122 female were included in the study. The prevalence of minor polypharmacy (2–4 drugs) accounted for 15.22%, major polypharmacy (≥5 drugs) for 81.35%, and hyper polypharmacy (≥10 drugs) for 3.46%. Most commonly prescribed drugs were vitamins, proton-pump inhibitors, antipyretic agents, and H2 receptor blockers. They accounted for 21.70%, 5.78%, 5.42%, and 4.94%, respectively. Conclusion: Polypharmacy is a preventable and can be rectified by prescribing appropriate medications. In future, a multidisciplinary approach which will be involving doctors, nurses, and pharmacists, shall be implemented for rational use of drugs in elderly patients.